Engineering Robust Ag‐Decorated Polydopamine Nano‐Photothermal Platforms to Combat Bacterial Infection and Prompt Wound Healing - Qi, Xiaoliang; Huang, Yijing; You, Shengye; Xiang, Yajing; Cai, Erya; Mao, Ruiting; Pan, Wenhao; Tong, Xianqin; Dong, Wei; Ye, Fangfu; Shen, Jianliang (Advanced science, 2022)
Polydopamine (PDA) nanoparticles have emerged as an attractive biomimetic photothermal agent in photothermal antibacterial therapy due to their ease of synthesis, good biodegradability, long‐term safety, and excellent photostability. However, the therapeutic effects of PDA nanoparticles are generally limited by the low photothermal conversion efficiency (PCE). Herein, PDA@Ag nanoparticles are synthesized via growing Ag on the surface of PDA nanoparticles and then encapsulated into a cationic guar gum (CG) hydrogel network. The optimized CG/PDA@Ag platform exhibits a high PCE (38.2%), which is more than two times higher than that of pure PDA (16.6%). More importantly, the formulated CG/PDA@Ag hydrogel with many active groups can capture and kill bacteria through effective interactions between hydrogel and bacteria, thereby benefiting the antibacterial effect. As anticipated, the designed CG/PDA@Ag system combined the advantages of PDA@Ag nanoparticles (high PCE) and hydrogel (preventing aggregation of PDA@Ag nanoparticles and possessing inherent antibacterial ability) is demonstrated to have superior antibacterial efficacy both in vitro and in vivo. This study develops a facile approach to boost the PCE of PDA for photothermal antibacterial therapy, providing a significant step forward in advancing the application of PDA nano‐photothermal agents. This work presents a facile and convenient strategy to boost the photothermal conversion efficiency of polydopamine (PDA) nanomaterials via growing Ag nanoparticles on the surface of PDA and then encapsulated into a cationic guar gum hydrogel network. The resultant system possesses robust photothermal performance that effectively kills bacteria and promotes wound healing.